Netrin‐G2 dysfunction causes a Rett‐like phenotype with areflexia. Issue 2 (15th November 2019) - Heimer, Gali; van Woerden, Geeske M.; Barel, Ortal; Marek‐Yagel, Dina; Kol, Nitzan; Munting, Johannes B.; Borghei, Minoeshka; Atawneh, Osama M.; Nissenkorn, Andreea; Rechavi, Gideon; Anikster, Yair; Elgersma, Ype; et al.
Abstract: We describe the underlying genetic cause of a novel Rett‐like phenotype accompanied by areflexia in three methyl‐CpG‐binding protein 2‐negative individuals from two unrelated families. Discovery analysis was performed using whole‐exome sequencing followed by Sanger sequencing for validation and segregation. Functional studies using short‐hairpin RNA for targeted gene knockdown were implemented by the transfection of mouse cultured primary hippocampal neurons and in vivo by in utero electroporation. All patients shared a common homozygous frameshift mutation (chr9:135073515, c.376dupT, p.(Ser126PhefsTer241)) in netrin‐G2 ( NTNG2, NM_032536.3) with predicted nonsense‐mediated decay. The mutation fully segregated with the disease in both families. The knockdown of either NTNG2 or the related netrin‐G family member NTNG1 resulted in severe neurodevelopmental defects of neuronal morphology and migration. While NTNG1 has previously been linked to a Rett syndrome (RTT)‐like phenotype, this is the first description of a RTT‐like phenotype caused by NTNG2 mutation. Netrin‐G proteins have been shown to be required for proper axonal guidance during early brain development and involved in N ‐methyl‐ d ‐aspartate‐mediated synaptic transmission. Our results demonstrating that knockdown of murine NTNG2 causes severe impairments of neuronal morphology and cortical migration are consistent with those of RTT animal models and the shared neurodevelopmental phenotypes between the individuals described here and typical RTT patients.